Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s12032-009-9244-6
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for “Triple Negative” breast cancer: a review of current practice and future outlook

Abstract: Patients with breast cancer who achieve a complete pathologic response (pCR) after preoperative (neoadjuvant) chemotherapy have an improved prognosis compared to those with residual disease; pCR being a good surrogate of long-term survival and cure from breast cancer. Despite their relative chemosensitivity, less than 25% of all patients with HER2/neu negative (0-2+), and hormone receptors (HR) negative tumors, so-called "Triple Negative" breast cancer (TNBC) treated with standard preoperative chemotherapy ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Furthermore, the prognostic value of LC3B was most significant in patients with TNBC. TNBC is the biologic entity that lacks ER, PR, and HER-2 expression; although TNBC is initially chemosensitive to NCT, patients with non-pCR with residual TNBC disease generally have an unfavorable prognosis with a short RFS and OS (30). Furthermore, several reports have suggested that TNBC represents a heterogeneous group comprising subtypes with different outcomes (31)(32)(33), as TNBC with The prognostic value of LC3B was most significant among patients with TNBC for both RFS and OS (P ¼ 0.007 and 0.006, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prognostic value of LC3B was most significant in patients with TNBC. TNBC is the biologic entity that lacks ER, PR, and HER-2 expression; although TNBC is initially chemosensitive to NCT, patients with non-pCR with residual TNBC disease generally have an unfavorable prognosis with a short RFS and OS (30). Furthermore, several reports have suggested that TNBC represents a heterogeneous group comprising subtypes with different outcomes (31)(32)(33), as TNBC with The prognostic value of LC3B was most significant among patients with TNBC for both RFS and OS (P ¼ 0.007 and 0.006, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…TNBC is a subtype of breast cancer. Although TNBC is an initially chemosensitive disease, less than 25% of patients with TNBC who received standard NAC achieved pCR and the remaining patients usually have a poor prognosis (9). Several approaches have been reported to improve the NAC efficacy in previous studies, including different anthracycline-based regimens, anthracycline-taxane combinations, sequential regimens and dose-dense schedules (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although TNBC is an initially chemosensitive disease, less than 25% of patients with TNBC who received standard NAC achieved pCR and the remaining patients usually have a poor prognosis (9). Several approaches have been reported to improve the NAC efficacy in previous studies, including different anthracycline-based regimens, anthracycline-taxane combinations, sequential regimens and dose-dense schedules (9). Furthermore, certain researchers have revealed other characteristics of TNBC, including overexpression of EGFR and c-KIT, increased proliferative rate through MAP kinase and Akt pathways (10) and providing some basis for the targeted therapy in those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current chemotherapeutic regimens continue to rely on heavy dosing to overcome their low cancer specificity and poor penetration [13][14][15]. Immunotargeting strategies have aided tumor targeting, but they still fall short of being substantially efficacious across a wide range of tumor types and are often limited in their scope because of the specificity of their targets [16,17].…”
Section: Introductionmentioning
confidence: 99%